Culturing Chinese hamster ovary cells on cyclo olefin polymer triggers epithelial‐mesenchymal transition and spheroid formation, which increases the foreign gene expression driven by the Moloney murine leukemia virus long terminal repeat promoter. (31st May 2021) - Hirano, Takaaki; Adachi, Satoru; Ichimura, Naoya; Kasai, Akira; Kobayashi, Masashi; Okuda, Takashi; Ogawa, Ryohei; Kagiya, Go
Abstract: Chinese hamster ovary (CHO) cells are frequently used for recombinant protein production (RPP) as a host. While the RPP has been proven successful, there is still a compelling need for further improvement. Cyclo olefin polymer (COP) is a plastic material widely utilized due to its properties including its low protein absorption. We applied this as a raw material for RPP cell culture to see if the COP is suitable. A recombinant CHO cell line expressing the human erythropoietin (hEPO) gene under the control of the Moloney murine leukemia virus‐long terminal repeat (MMLV‐LTR) was established. When the cells were cultured in a dish made from COP, the cells attached to the bottom, and then started to float and form spheroids. RNASeq data analysis suggested the epithelial‐mesenchymal transition (EMT) was triggered with receptor tyrosine kinase activation shortly after cultivation. It coincided with the hEPO transcription increase. After the cell floating, though EMT marker gene expression subsided, a hEPO expression increase sustained. When fibronectin was applied to COP dish surface, the cell floating was suppressed and hEPO expression decreased. We then treated cells with MβCD, a drug that destroys the lipid raft, eliminating molecules in the raft. This facilitated cell floating and spheroid formation coincided with hEPO expression enhancement. These results suggest interactions between a cell and COP surface might trigger the EMT and the subsequent event, both of which activated the MMLV‐LTR promoter. Thus, employing COP for culturing cells, a potent RPP system could be established with its advantage for efficient protein purification.